Safety and feasibility of a 1 frame-per-second X-ray framerate in cardiac electrophysiology. (1st March 2021) - Deubner, Nikolas; Ziakos, Athanasios; Greiss, Harald; Sezenias, Angelis; Seyfarth, Melchior; Sause, Armin
Abstract: Background: We investigated the feasibility and safety of a framerate of 1 frame per second ("fps") for fluoroscopy and cine-angiography, to lower radiation exposure for patients and personnel in cardiac electrophysiology ("EP"). Method: Analysis of 2521 EP procedures, 899 (36%) with the lowest available conventional framerate (3.75 fps) and 1622 (64%) procedures performed with a framerate lowered further to 1.0 fps (by looping a 1 Hz square pulse to the ECG trigger) performed between 01/2016 and 01/2020. Results: Procedures performed with 1.0 fps had the same acute procedural success rates ( p  = 0.20) and adverse event rates ( p  = 0.34) as the 3.75 fps group. There was no difference in total X-ray operation time ( p  = 0.40). The dose-area-product (DAP) was significantly reduced from 638 to 316 cGy*cm 2 (p < < 0.0001) for all procedure types together, and for each subgroup. In a multivariable linear regression model, total X-ray operation time (estimate 38 cGy*cm 2 /min) and body mass index (estimate 32 cGy*cm 2 / index point) and a framerate of 1.0 fps (−314 cGy*cm 2 against 3.75 fps) were independent predictors of a lower DAP ( p -value of t-statistic for all << 0.0001). Conclusions: A framerate of 1.0 fps is safe and feasible in cardiac electrophysiology procedures. It was associated with a significant reduction of radiation exposure for patient and personnel. Highlights: Radiation exposure can significantly be lowered for cardiac electrophysiology procedures without compromising success or safety Use of the ECG trigger input allows very low framerates in fluoroscopy workplaces originally designed for higher framerates When correcting for body-mass-index and total X-ray operation time, framerate proves to be an independent predictor for dose-area-product